A layered double hydroxide-derived exchange spring magnet array grown on graphene and its application as an ultrathin electromagnetic wave absorbing material. Issue 39 (25th September 2019) - Zhao, Xiaonan; Nie, Xiaoyu; Li, Ya; Pu, Yanhui; Sun, Xin; Yu, Ronghai; Liu, Xiaofang; Shui, Jianglan
Abstract : An exchange spring magnet/N-doped graphene composite is synthesized as an ultrathin and highly efficient electromagnetic wave absorbing material utilizing the exchange coupling effect between hard/soft magnetic phases. Abstract : The combination of exchange spring magnets with graphene sheets is expected to be an effective method for preparing an ultrathin electromagnetic wave absorber. However, the synthesis of such a composite is still a challenge and has not yet been explored. Herein, a layered double hydroxide (LDH) array is used for the first time as a precursor for an exchange spring magnet. By controllable annealing of CoFe LDH array/graphene oxide precursors in an NH3 atmosphere, we synthesize CoFe alloy/nitrides/N-doped graphene composites. The magnetic exchange coupling between soft magnetic phases (Co7 Fe3, Co5.47 N) and the hard magnetic phase (Fe3 N) improves the magnetic loss in the high-frequency region. Moreover, the heterogeneous interfaces between multiple phases generate strong interfacial polarization loss, and the N incorporation in graphene causes large conductive loss and dipole polarization loss. The composite exhibits an extremely strong electromagnetic wave absorption performance with a reflection loss of −59.1 dB at an ultrathin layer thickness of 1.4 mm. Remarkably, its specific reflection loss value (reflection loss/thickness) achieves a new record among all the magnetic nanomaterial–graphene composite absorbers, which implies its potential application as an excellent ultrathin EMW absorbing layer. This study provides a new method to prepare an exchange spring magnet and highlights the importance of magnetic exchange coupling in improving electromagnetic wave absorption.